Patterns of Dysmenorrhea and Self-management Strategies among University Students - Iffat Imran, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To explore the frequency of dysmenorrhea, its characteristics and impact on university students' education and their coping behaviours. Study Design: Descriptive cross-sectional study. Place and Duration of Study: The Main Campus, AlHawiyya Taif University, Saudi Arabia from 1st October 2020 to 31st December 2020. Methodology: Three hundred and eighty university students were enrolled. Data was collected via a self-reported electronic questionnaire. The required information was grouped into three sections, section A about socio-demographic data, section B about details of dysmenorrhea like onset, duration, severity, presentation, and its effect on their studies, and section C about their coping strategies of dysmenorrhea were recorded. The pain severity was scored on a Visual Analogue Scale (VAS). Results: The frequency of dysmenorrhea was 72%. Low backache 55.7% and nervousness 47.2% were the most frequent somatic and affective symptoms, respectively. Duration and severity had a significant association while BMI had no association with dysmenorrhea. Most students used a combination of treatment methods. Abstinence and academic activities affecting due to dysmenorrhea were found positive association. Conclusion Dysmenorrhea is a highly prevalent health issue negatively affecting students’ academic performance. Strategies should be planned at an institutional level to increase awareness about its pathophysiology and management to improve students’ behaviour. Keywords: Dysmenorrhea, University students, Self-medication, Analgesia